The experience of living in a nursing home : Literature review and summary of key issues raised with the Patient and Client Council Complaints Service.: Literature review and summary of key issues raised with the Patient and Client Council Complaints Service. ([2018]) - Patient and Client Council (Northern Ireland),
No abstract available